Finerenone: From the Mechanism of Action to Clinical Use in Kidney Disease - Nejc Piko; Sebastjan Bevc; Radovan Hojs; Robert Ekart (MDPI AG, 2024)
Diabetic kidney disease is a frequent microvascular complication of diabetes and is currently the leading cause of chronic kidney disease and end-stage kidney disease worldwide. Although the prevalence of other complications of diabetes is falling, the number of diabetic patients with end-stage kidney disease in need of kidney replacement therapy is rising. In addition, these patients have extremely high cardiovascular risk. It is more than evident that there is a high unmet treatment need in patients with diabetic kidney disease. Finerenone is a novel nonsteroidal mineralocorticoid receptor antagonist used for treating diabetic kidney disease. It has predominant anti-fibrotic and anti-inflammatory effects and exhibits several renal and cardiac protective effects. This review article summarizes the current knowledge and future prospects of finerenone in treating patients with kidney disease.